Optimisation of nursery rearing for megalopa of giant mud crab Scylla serrata (Forskal, 1775) - Antony, Jose; Balasubramanian, C. P.; Balamurugan, J.; Sandeep, K. P.; Biju, I. F.; Vijayan, K. K. (Indian Journal of Fisheries, 2019)
Three nursery rearing trials were conducted to overcome the inconsistent survival of megalopa of the giant mud crab Scylla serrata (Forskal, 1775) during metamorphosis to crab instar. In the first trial, 3-4 days old megalopa (4.73 mg mean body weight) were stocked in hapas erected in outdoor brackishwater ponds and indoor fiberglass (FRP) tanks at densities of 500 nos. m-2 and 1 no. l-1 respectively and reared for 15 days using minced clam meat (Meretrix casta) as feed. Outdoor hapas were provided with seaweed, Gracilaria tenuistipitata as shelter. Mean survival rate of crab instar following three consecutive runs were significantly higher (p<0.05) for megalopa reared in outdoor hapas (57.7±2.7%) over indoor FRP tanks (24.1±2.2%). To ascertain the life stage that yields optimal survival on weaning from indoor hatchery to ponds, zoea 5 (Z5) and megalopa 1-day old (M1), 2-day old (M2), 3-day old (M3) and 4-day old (M4) were reared in hapas for15 days and fed on minced clam meat. Three day and 4-day old megalopa demonstrated significantly higher survival rates (p<0.05) of 62.3±3.08% and 69.6±2.35% respectively to crab instar stage at conclusion of the trial. Megalopa (3-4 days old, 5.05 mg mean body weight) were stocked to 100 l tanks (stocking density - 1 no. 4 l-1) and reared for a period of 8 days using different feeds viz., artemia biomass (T1), minced clam meat (T2), crab larvae (T3) and artemia nauplii (T4) in the third trial to evaluate various production parameters. Crab instar conversion rate (number of crab instars/number of megalopa stocked × 100) was significantly higher (p<0.0001) for megalopa fed using artemia biomass (T1) and minced clam meat (T2) at 74.66±5.81% and 72.00±2.30% respectively. Results of the present study indicate that, high density rearing (500 no. m-2) of megalopa (3-4 days old) in outdoor hapas provided with seaweed refuge for short periods (15 days) would yield higher survival rate to crab stage. Nursery rearing of megalopa in ponds reduces the hatchery phase in mud crab larval rearing and maximise production of crab instars.